KETERAMPILAN INTERPERSONAL : UPAYA MENCIPTAKAN KOMUNIKASI EFEKTIF - Kurniasih, Yuni (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: A good communication will create a good impression of nurses. Thus, the nursing care objectives will be achieved. The articles were gathered through Sciendirect, PubMed and Ebscho. The search through Sciendirect, PubMed, and Ebscho were conducted using advanced search with keyword interpersonal skills, nursing and effective communication. The method used in the article was mixed methods (qualitative and quantitative methods). The results obtained 3 articles which were relevant with the inclusion criteria in which every article produced some themes. The nurses’ interpersonal skills would have an impact on the ability to communicate. The ability to communicate is a core value which must be mastered by a nurse to meet the needs of patients and keep the patient safety.Keywords: nurses, interpersonal skills, communication